Beninese vaccination clinic (Canadian Medical Education Journal, 2017)
This photo was taken in the village of Ladji, which is on the outskirts of Cotonou, the capital of Benin. At the time, I was a second year medical student volunteering at a local medical clinic. On every Wednesday morning, many Beninese babies, like this one, cry out of discomfort while receiving their monthly vaccinations. The photo shows a local clinic nurse administering the vaccination.